(untitled) (Research, Society and Development, 2021)
This study presents an overview of the production of quail eggs in the state of Pará, based on an analysis of production in the period 2000-2019 using secondary data from the time series of egg production and the number of quail heads / beaks obtained with the IBGE Database. The Locational Quotient (LQ) indexes that indicate the specialization of a region in a given activity or sector and the Locational Gini Coefficient (LGC) that identifies the spatial concentration were estimated. The results of the study show that in the period analyzed, the Metropolitan Mesoregion of Belém lost its participatory power in Pará production, placing the Southeast and Southwest Paraense mesoregions with the highest concentration of production in the state. The municipalities of Altamira, Paragominas and Santarém present themselves as the largest producers of quail eggs in the state of Pará. Despite this, the production of quail eggs in Pará, in recent years, has been declining and reducing the specialized micro-regions, high spatial concentration.